FAO technical guidelines for responsible fisheries N3: Intergration of fisheries into coastal area management - FAO (FAO, 1996)
The guidelines are provided as explanatory material to Article 10 in the Code of Conduct for Responsible Fisheries Articles 10 concerns the Integration of Fisheries into Coastal Management in order to assist in achieving the national use of scarce coastal resources. In particular, they address the issue of how the fisheries sector can be integrated into coastal management planning so that interactions between the fisheries sector and other sectors can be taken account in the establishment of management policy and practice with regard to coastal resources.